Autosomal Recessive Primary Microcephaly: Not Just a Small Brain - Zaqout, Sami; Kaindl, Angela M. (Frontiers in Cell and Developmental Biology, 2022)
Microcephaly or reduced head circumference result from a multitude of abnormal developmental processes affecting brain growth and/or leading to brain atrophy. Autosomal recessive primary microcephaly (MCPH) is the prototype of isolated primary (congenital) microcephaly, affecting predominantly the cerebral cortex. For MCPH, an accelerating number of mutated genes emerge annually, and they are involved in crucial steps of neurogenesis. In this review article, we provide a deeper look into the microcephalic MCPH brain. We explore cytoarchitecture focusing on the cerebral cortex and discuss diverse processes occurring at the level of neural progenitors, early generated and mature neurons and glial cells. We aim to thereby give an overview on current knowledge in MCPH phenotype and normal brain growth.